College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 1 - Section 1.4 - Quadratic Equations - 1.4 Exercises: 41

Answer

$x=\left\{ 1-\sqrt{3},1+\sqrt{3} \right\}$

Work Step by Step

$\bf{\text{Solution Outline:}}$ To solve the given equation, $ x^2-2x-2=0 ,$ using the completing the square method, ensure first that the coefficient of the squared variable is $1.$ Then express the equation in the form $x^2+bx=c.$ Next step is to add the quantity $\left( \dfrac{b}{2} \right)^2$ to both sides. Factor the resulting perfect square trinomial at the left side of the equal sign. Then take the square root of both sides. Finally, solve for the value of the variable. $\bf{\text{Solution Details:}}$ Expressing the equation above in the form $x^2+bx=c$ results to \begin{array}{l}\require{cancel} x^2-2x=2 .\end{array} Making the left side a perfect square trinomial by adding the quantity $ \left( \dfrac{b}{2} \right)^2 $ to both sides results to \begin{array}{l}\require{cancel} x^2-2x+\left( -\dfrac{2}{2} \right)^2=2+\left( -\dfrac{2}{2} \right)^2 \\\\ x^2-2x+\left( -1 \right)^2=2+\left( -1 \right)^2 \\\\ x^2-2x+1=2+1 \\\\ (x-1)^2=3 .\end{array} Taking the square root of both sides and then isolating the variable result to \begin{array}{l}\require{cancel} x-1=\pm\sqrt{3} \\\\ x=1\pm\sqrt{3} .\end{array} The solutions are \begin{array}{l}\require{cancel} x=1-\sqrt{3} ,\\\\\text{ OR }\\\\ x=1+\sqrt{3} .\end{array} Hence, $ x=\left\{ 1-\sqrt{3},1+\sqrt{3} \right\} .$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.